Polycystin-2 Is Required for Starvation- and Rapamycin-Induced Atrophy in Myotubes - Kretschmar, Catalina; Peña-Oyarzun, Daniel; Hernando, Cecilia; Hernández-Moya, Nadia; Molina-Berríos, Alfredo; Hernández-Cáceres, María Paz; Lavandero, Sergio; Budini, Mauricio; Morselli, Eugenia; Parra, Valentina; Troncoso, Rodrigo; Criollo, Alfredo (Frontiers in Endocrinology, 2019)
Muscle atrophy involves a massive catabolism of intracellular components leading to a significant reduction in cellular and tissue volume. In this regard, autophagy, an intracellular mechanism that degrades proteins and organelles, has been implicated with muscle breakdown. Recently, it has shown that polycystin-2 (PC2), a membrane protein that belongs to the transient receptor potential (TRP) family, is required for the maintenance of cellular proteostasis, by regulating autophagy in several cell types. The role of PC2 in the control of atrophy and autophagy in skeletal muscle remains unknown. Here, we show that PC2 is required for the induction of atrophy in C2C12 myotubes caused by nutrient deprivation or rapamycin exposure. Consistently, overexpression of PC2 induces atrophy in C2C12 myotubes as indicated by decreasing of the myogenic proteins myogenin and caveolin-3. In addition, we show that inhibition of mTORC1, by starvation or rapamycin is inhibited in cells when PC2 is silenced. Importantly, even if PC2 regulates mTORC1, our results show that the regulation of atrophy by PC2 is independent of autophagy. This study provides novel evidence regarding the role of PC2 in skeletal muscle cell atrophy.